1995
DOI: 10.1159/000188587
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow Transplant Nephropathy: Radiation Nephritis Revisited

Abstract: Late-onset renal failure occurs in up to 20% of survivors of bone marrow transplantation. Total body irradiation is a major factor in this syndrome, so-called bone marrow transplant nephropathy (BMT NP), which is defined by disproportionate anemia, hypertension, and azotemia. Previous or concurrent chemotherapy may potentiate the effect of radiation on the kidney. Kidney function may decline acutely or more gradually, with eventual long-term stabilization. Patient survival is associated with control of the blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
71
1
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(77 citation statements)
references
References 32 publications
4
71
1
1
Order By: Relevance
“…11 The higher dose of TBI needs to be considered in interpreting our results because models of transplantation have shown that the renal insufficiency after BMT appears to be a form of radiation nephritis. 3 Degree of renal injury observed in our patients who were not shielded is unlikely to be seen in patients who receive 12 Gy TBI, and the importance of renal shielding or genotype might not be apparent in subjects irradiated to 12 Gy TBI or less.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…11 The higher dose of TBI needs to be considered in interpreting our results because models of transplantation have shown that the renal insufficiency after BMT appears to be a form of radiation nephritis. 3 Degree of renal injury observed in our patients who were not shielded is unlikely to be seen in patients who receive 12 Gy TBI, and the importance of renal shielding or genotype might not be apparent in subjects irradiated to 12 Gy TBI or less.…”
Section: Discussionmentioning
confidence: 67%
“…A distinct syndrome of chronic renal failure after BMT termed 'bone marrow transplant nephropathy' has been described that consists of azotemia, disproportionate anemia, and hypertension. 2,3 This syndrome is thought to be due to either microvascular or renal parenchymal damage from the preparative regimen and in its most severe form resembles hemolytic uremic syndrome (HUS).Studies using animal models of BMT nephropathy have shown that angiotensin converting enzyme (ACE) inhibitors can effectively prevent and treat the syndrome. 4,5 This finding implicates the renin-angiotensin axis in the pathogenesis of the disorder.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Late nephropathy with rapid deterioration of renal function can present acutely in association with haemolytic anaemia, while chronic onset may occur after gradual decline in kidney function. 32 Irradiation and in particular TBI in combination with immunosuppressive and supportive medication represent the main risk factors for patients who developed chronic renal impairment. 33 Miralbell et al 34 reported renal dysfunction after allogeneic HSCT strongly related to TBI dose and GvHD.…”
Section: Renal Complicationsmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]technique and compared using an extension of the lowed by syngeneic BMT. An additional 11 animals Kruskal-Wallis test.…”
mentioning
confidence: 99%